Dust in the wind: How climate variables and volcanic dust affect rates of tooth wear in central american howling monkeys. Issue 2 (1st October 2015) - Spradley, Jackson P.; Glander, Kenneth E.; Kay, Richard F.
ABSTRACT: Objectives: Two factors have been considered important contributors to tooth wear: dietary abrasives in plant foods themselves and mineral particles adhering to ingested food. Each factor limits the functional life of teeth. Cross‐population studies of wear rates in a single species living in different habitats may point to the relative contributions of each factor. Materials and Methods: We examine macroscopic dental wear in populations of Alouatta palliata (Gray, 1849) from Costa Rica (115 specimens), Panama (19), and Nicaragua (56). The sites differ in mean annual precipitation, with the Panamanian sites receiving more than twice the precipitation of those in Costa Rica or Nicaragua (∼3, 500 mm vs. ∼1, 500 mm). Additionally, many of the Nicaraguan specimens were collected downwind of active plinian volcanoes. Molar wear is expressed as the ratio of exposed dentin area to tooth area; premolar wear was scored using a ranking system. Results: Despite substantial variation in environmental variables and the added presence of ash in some environments, molar wear rates do not differ significantly among the populations. Premolar wear, however, is greater in individuals collected downwind from active volcanoes compared with those living in environments that did not experience ash‐fall. Discussion: Volcanic ash seems to be an important contributor to anterior tooth wear but less so in molar wear. That wear is not found uniformly across the tooth row may be related to malformation in the premolars due to fluorosis. A surge of fluoride accompanying the volcanic ash may differentially affect the premolars as the molars fully mineralize early in the life of Alouatta . Am J Phys Anthropol 159:210–222, 2016. © 2015 Wiley Periodicals, Inc.